Multicompartment Block Polymer Micelles - Moughton, Adam O; Hillmyer, Marc A; Lodge, Timothy P (Macromolecules, 2012)
Multicompartment micelles are an intriguing class of self-assembled aggregates with subdivided solvophobic cores. They have been subject to extensive research in part due to their unique morphological and sequestration properties as a result of multiple distinct chemical environments being in close proximity within one nanostructure. Multicompartment micelles hold potential for use in various applications that include the therapeutic delivery of multiple incompatible drug payloads. The present Perspective reviews recent achievements in strategies for the synthesis, self-assembly, and morphological control of multicompartment micelles and highlights future challenges and potential applications.